Peran Instagram Terhadap Partisipasi Masyarakat Samarinda pada Donasi Online “Tolong Menolong Lawan Covid-19” - Nuryunita; Hairunnisa (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Instagram has many features that continue to innovate so that the application develops and switches its role to become a media for spreading information, one of the information that has been successfully shared via Instagram is the Online Donation "Tolong Menolong Lawan Covid-19" which is distributed by a influencer named Rachel Vennya. The purpose of this study is to analyze and describe the role of Instagram in the participation of the Samarinda people in this donation based on the elements of innovation diffusion. The methodology used in this research is qualitative research with a descriptive approach. There were informants who were obtained through a purposive sampling technique based on predetermined criteria. Data in this study uses techniques from Miles and Huberman. Based on the research results, there are main points, namely the decision process of innovation diffusion, that describe the process of accepting innovations that were passed by the informants.